2016
DOI: 10.1186/s12913-016-1708-8
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening patient safety in transitions of care: an emerging role for local medical centres in Norway

Abstract: BackgroundPatient safety has gained less attention in primary care in comparison to specialised care. We explore how local medical centres (LMCs) can play a role in strengthening patient safety, both locally and in transitions between care levels. LMCs represent a form of intermediate care organisation in Norway that is increasingly used as a strategy for integrated care policies. The analysis is based on institutional theory and general safety theories.MethodsA qualitative design was applied, involving 20 int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
1
Order By: Relevance
“…Studier viste ikke noen økt risiko for pasienter ved å motta desentralisert medisinsk behandling (8-10). Fragmentering av omsorg, et økt antall grensesnitt og pasientoverføringer kan likevel anses som en trussel mot pasientsikkerheten (11). Svakheter ved kommunikasjon og informasjonsoverføring ved utskrivelse fra sykehuset er vanlig og kan påvirke pasientomsorgen negativt (12).…”
Section: Oppgavefordeling Og Organiseringunclassified
“…Studier viste ikke noen økt risiko for pasienter ved å motta desentralisert medisinsk behandling (8-10). Fragmentering av omsorg, et økt antall grensesnitt og pasientoverføringer kan likevel anses som en trussel mot pasientsikkerheten (11). Svakheter ved kommunikasjon og informasjonsoverføring ved utskrivelse fra sykehuset er vanlig og kan påvirke pasientomsorgen negativt (12).…”
Section: Oppgavefordeling Og Organiseringunclassified
“…A review of the Cochrane library identified 19 publicationsnone of the studies used the term redundancy in line with the inclusion criteria. Several publications (Kongsvik, Halvorsen, Osmundsen, & Gjøsund, 2016;Penchansky & Macnee, 1993;Trevino et al, 2018;Van Spall, Kassam, & Tollefson, 2015;Watkins, Tirabassi, & Aversano, 2006) reference generic principles of redundancy in safer systems as codified and adapted from Sutcliffe (Sutcliffe, 2011). The remaining manuscripts listed examples of redundancy to structures and processes of healthcare (Donabedian, 1988).…”
Section: Critical Review Of Modular Redundancy In Healthcarementioning
confidence: 99%
“…This is partly related to more structured efforts to measure patient harm, which have revealed the magnitude of the problem. The insights from the report ‘To err is human’, and similar reports from other countries, instigated a variety of programmes, on both the global and national levels [9]. Review studies show that the median incidence rate of in-hospital adverse events ranges from 9 to 10%, with considerable variations between the reviewed studies [10, 11].…”
Section: Introductionmentioning
confidence: 99%